2012
DOI: 10.1186/1878-5085-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Introduction into PPPM as a new paradigm of public health service: an integrative view

Abstract: In the present state of healthcare, usual medical care is generally given to the already diseased person, while the key link—personal health monitoring underlain by predictive, preventive, and personalised medicine (PPPM) techniques that are being intensively elaborated worldwide—is simply missing. It is this link, based on the recognition of subclinical conditions, prediction, and further preventive measures, that is capable of regulating morbidity and diminishing the rates of disability among able-bodied pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Large-scale testing and comparative analysis of different PCR-based and CRISPR diagnostic systems in the real world is mandatory to move new methods into laboratory and field diagnostics. Introducing CRISPR diagnostic tools into practice may improve control over infectious diseases, prevent their rapid spread, introduce diagnostic testing to finally enter the era of precise and personalized medicine 67 , expand the use of massive population screening, and better control outbreaks of infectious diseases, including outbreaks in remote geographic areas. Timely, inexpensive, high-quality diagnosis of infectious and non-infectious diseases by rapid and readily available tests will certainly have a pronounced positive impact on human health on the global level, reducing morbidity and mortality.…”
Section: Pcr V Crispr-casmentioning
confidence: 99%
“…Large-scale testing and comparative analysis of different PCR-based and CRISPR diagnostic systems in the real world is mandatory to move new methods into laboratory and field diagnostics. Introducing CRISPR diagnostic tools into practice may improve control over infectious diseases, prevent their rapid spread, introduce diagnostic testing to finally enter the era of precise and personalized medicine 67 , expand the use of massive population screening, and better control outbreaks of infectious diseases, including outbreaks in remote geographic areas. Timely, inexpensive, high-quality diagnosis of infectious and non-infectious diseases by rapid and readily available tests will certainly have a pronounced positive impact on human health on the global level, reducing morbidity and mortality.…”
Section: Pcr V Crispr-casmentioning
confidence: 99%
“…Complete diagnostics of the organism, the creation of individual genetic passports, development and correction of treatment strategies based on the individual features of genetics, metabolism, microbiota of particular organism-all these tasks are belongs to PPPM. However, holding such a colossal amount of expensive and complicated research would be impossible without translation of the latest scientific achievements into practical medicine [3] [6]- [8] (Figure 3).…”
Section: Fundamentals Of Pppmmentioning
confidence: 99%
“…Over the course of its history, medical science was much more focused on the treatment of clinical illnesses that have already arisen, than on detecting and preventing their occurrence. Practical experience over many years has shown that this approach is often ineffective against a number of diseases, and also requires a great deal of expenses [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations